The influence of parenting on the incidence of stunting in toddlers aged 1-3 year - Flaviani Angela Nita; Evy Ernawati; Fatimah Sari; Juda Julia Kristiarini; Indah Purnamasari (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Parenting is a method used to help children grow and develop by caring for, educating, and guiding them so that children achieve their independence. Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. This study aims to determine the influence of parenting on the incidence of stunting in toddlers aged 1-3 years. This type of research is descriptive-analytic, using quantitative methods of cross-sectional design. The total population in this study was 64 people. The sample in this study amounted to 35 people, sampling using purposive sampling. The results of the study showed that most of them had applied parenting styles in caring for toddlers in daily life with sufficient categories of 30 people, 85.7%. Children who experienced stunting 1 as many as 22 people, 62.8% with 2 categories and those who did not experience stunting as many as 13 people 37.2%. Based on the results of the chi-square test, it was found that there was an influence of parenting on the incidence of stunting with a p-value of 0.025. It can be concluded that there is an influence of parenting on the incidence of stunting. Parenting is quite sufficient, becoming one of the challenges for health workers. There is still a need to provide education to parents in increasing knowledge about parenting and stunting.